2019
DOI: 10.1063/1.5092729
|View full text |Cite
|
Sign up to set email alerts
|

Effect of doping mechanism on photogenerated carriers behavior in Cu-doped ZnSe/ZnS/L-Cys core-shell quantum dots

Abstract: Cu-doped ZnSe/ZnS/L-Cys core–shell QDs are prepared by both nucleation doping and growth doping in an aqueous synthesis method. Transport of photogenerated free charge carriers (FCCs) in these Cu-doped QDs is probed via a combination of surface photovoltaic (SPV), photoacoustic (PA), and electric-field-induced SPV techniques, supplemented by the UV–VIS absorption spectrum and Raman spectrum. The results confirm that the two doping mechanisms result in different doping locations and microelectronic structures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The incorporation of a small amount of a dopant impurity in wide bandgap semiconductors like zinc chalcogenides allows to modify the electronic states into the bandgap which provides to doped-QDs unique advantages such as minimum self-absorption due to a large Stokes shift, longer excited-state lifetime and high thermal and photostability [32][33][34]. Recently, the Cudoping of ZnS and ZnSe QDs has been investigated and it was demonstrated that the relaxation of the exciton occurs via the t2 energy states of Cu 2+ resulting in an emission in the green region valuable for applications such as bio-imaging, sensing, photocatalysis and light emitting devices [35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Gradient alloyed ZnSeS QDs are well-known to exhibit improved optical properties and higher stability compared to binary ZnS or ZnSe QDs [49][50][51][52][53] but their doping with Cu has only scarcely been investigated [54,55].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of a small amount of a dopant impurity in wide bandgap semiconductors like zinc chalcogenides allows to modify the electronic states into the bandgap which provides to doped-QDs unique advantages such as minimum self-absorption due to a large Stokes shift, longer excited-state lifetime and high thermal and photostability [32][33][34]. Recently, the Cudoping of ZnS and ZnSe QDs has been investigated and it was demonstrated that the relaxation of the exciton occurs via the t2 energy states of Cu 2+ resulting in an emission in the green region valuable for applications such as bio-imaging, sensing, photocatalysis and light emitting devices [35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Gradient alloyed ZnSeS QDs are well-known to exhibit improved optical properties and higher stability compared to binary ZnS or ZnSe QDs [49][50][51][52][53] but their doping with Cu has only scarcely been investigated [54,55].…”
Section: Introductionmentioning
confidence: 99%
“…3,7−9 In this context, ZnSe QDs have been used in the development of more complex nanomaterials including ZnSe/ZnS core/shell heterostructures, 7 ZnSeTe-alloyed QDs, 10 and Cu-or Mn-doped ZnSe/ ZnS QDs. 11,12 To precisely fabricate QD-containing devices or synthesize complex nanostructures, 13 it is necessary to know the core QD size and concentration in solution. Empirical fit equations correlating the position of the lowest-energy electron transition (1S peak) to the QD size and its molar extinction coefficient (ε 1S ) are often used to quickly, economically, and nondestructively characterize QD samples.…”
mentioning
confidence: 99%
“…Their color tunability, narrow emission spectra, high quantum yield, and chemical and photostability have resulted in their extensive use in optoelectronic devices, as well as in biosensing and biomedical imaging applications. As the application of QDs grows in mass-produced consumer electronics and sensitive biological applications, interest in heavy metal-free compositions increases as well. With a bulk band gap of 460 nm (2.7 eV), colloidal ZnSe-based QDs are a leading candidate for the fabrication of violet and blue LEDs, displays, and laser diodes, making the synthetic development of these nanoparticles technologically important. , In this context, ZnSe QDs have been used in the development of more complex nanomaterials including ZnSe/ZnS core/shell heterostructures, ZnSeTe-alloyed QDs, and Cu- or Mn-doped ZnSe/ZnS QDs. , …”
mentioning
confidence: 99%
“…10 As a result of the quantum confinement effect arising from a reduction in the QD diameter below its exciton Bohr radius, the optical properties of ZnSe nanoparticles can be precisely tuned by altering their size. ZnSe/ZnS core/shell heterostructures, 7 ZnSeTe alloyed QDs 11 , and Cu-or Mn-doped ZnSe/ZnS QDs 12,13 have been used for the fabrication of ZnSe-based QLEDs. In order to precisely fabricate QDcontaining devices or synthesize complex nanostructures, it is necessary to know the core QD size and concentration in solution.…”
mentioning
confidence: 99%